2014
DOI: 10.1111/jpn.12237
|View full text |Cite
|
Sign up to set email alerts
|

High levels of whole raw soybean in diets for Nellore bulls in feedlot: effect on growth performance, carcass traits and meat quality

Abstract: The objective of this study was to evaluate the effect of whole raw soybean (WRS) in the finishing diet of Nellore cattle on productive performance, carcass traits, meat quality, fatty acid profile of meat, and blood parameters. In a completely randomized design, 52 Nellore bulls (mean body weight ± SD: 380 ± 34 kg) were allotted for 84 days. The animals received the following diets with a forage: concentrate ratio of 40/60: (i) WRS0: control diet without soybean grains; (ii) WRS8: diet containing 8% WRS in dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 23 publications
(30 reference statements)
5
18
0
Order By: Relevance
“…Fat supplementation increases lipoprotein cholesterol export by the intestine, the major site of cholesterol synthesis in ruminants (Noble, 1981). Cônsolo et al (2015) fed increasing doses of WS to Nellore bulls and found a linear increase in total cholesterol and no difference in glucose concentrations. The mechanism by which CHI alters the cholesterol metabolism is unclear, but studies in humans have demonstrated that chitosan reduced serum LDL cholesterol (Yihua and Binglin, 1997;Wuolijoki et al, 1999), and Bokura and Kobayashi (2003) suggested a reduced lipid absorption from the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Fat supplementation increases lipoprotein cholesterol export by the intestine, the major site of cholesterol synthesis in ruminants (Noble, 1981). Cônsolo et al (2015) fed increasing doses of WS to Nellore bulls and found a linear increase in total cholesterol and no difference in glucose concentrations. The mechanism by which CHI alters the cholesterol metabolism is unclear, but studies in humans have demonstrated that chitosan reduced serum LDL cholesterol (Yihua and Binglin, 1997;Wuolijoki et al, 1999), and Bokura and Kobayashi (2003) suggested a reduced lipid absorption from the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Shear force (SF) and cooking loss (CL) analysis SF and CL were determined at the Laboratory of Meat Quality of the University of São Paulo, using the methodology proposed by Wheeler et al (2001) and previously described by Cônsolo et al (2015). The steaks were thawed for 24 h at 4°C, weighed and roasted in an oven equipped with a thermostat adjusted to 170°C (Flexa de Ouro Industry, São Paulo, SP, Brazil).…”
Section: -11th Rib Compositionmentioning
confidence: 99%
“…6 L* = Lightness, from 0 (black) to 100 (white); a* = redness, from -120 (green) to 120 (red); b*=yellowness, from -120 (blue) to 120 (yellow). Fonte: Cônsolo, 2015 Meat colour scores were not affected by RH supplementation, and values were within the accepted normal range . Dietary CP altered the b* value (P<0.01), being greater for CP120 than CP100 (15.3 vs. 10.2 for CP120 and CP100, respectively).…”
Section: Carcass Traits and Meat Qualitysupporting
confidence: 53%
“…After 14 and 21 days of aging, cooking losses were lower than at day 0 (P<0.05, Figure 1). Fonte: Cônsolo, 2015 There was no RH x CP interaction for meat WBSF (P=0.13). There was a significant RH x Time interaction for meat WBSF (P<0.01, Figure 2).…”
Section: Carcass Traits and Meat Qualitymentioning
confidence: 93%
See 1 more Smart Citation